Being Ambitious About Emotions in Value Epistemology - Milona, Michael (Les ateliers de l'éthique / The Ethics Forum, 2024)
This commentary investigates chapter 7’s central thesis that emotions can be a source of immediate justification for evaluative beliefs. I focus on two key challenges to this thesis, one rooted in the purported unreliability of emotions and another in their own susceptibility to justification. My aim is to buttress the chapter’s responses to these challenges, charting promising avenues forward.